Real-world outcome and healthcare costs of relapsed or refractory multiple myeloma: A retrospective analysis from the Chinese experience. Issue 5 (27th May 2016) - Zhou, Xin; Xia, Jun; Mao, Jingjue; Cheng, Feng; Qian, Xifeng; Guo, Hongfeng
Abstract : Objectives : Our aim was to retrospectively investigate the real-world outcome and healthcare costs associated with the treatment of patients with relapsed or refractory multiple myeloma (RRMM) in a Chinese single center. Methods : A retrospective study was conducted for 93 patients between January 2008 and December 2013 in a Chinese hematology department. Total monthly costs attributable to each cost component were described across all regimens and for bortezomib-based treatment regimens. Results : Mean total cost per patient-month (1139.85) varied depending on the sequence of therapy (range: mean 51.63–6600.96). Drugs and hospital visit were the most and the least consumed resource (65.48% and 2.87%, respectively). Mean total monthly costs were 2071.96 (range: 679.73–6600.96) and 551.14 (range: 51.63–1698.59) for patients receiving bortezomib and patients not receiving bortezomib, respectively. Differences between the two groups were significant for drugs; drugs costs were higher for patients treated with bortezomib. Kaplan–Meier curves showed a longer overall survival (mean [median] 31.43 [25] vs. 21.93 [18] months) for patients treated with bortezomib. Conclusion : Real-world costs during treatment of RRMM varied greatly. Total costs during bortezomib-based regimens are significantly higher compared with non-bortezomib regimens. Further multi-center studies are needed to assess the cost-effectiveness of bortezomib for the treatment of RRMM in China.